2018
DOI: 10.1007/s13201-018-0686-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influence of lineaments, lineament intersections and geology on groundwater yield in the basement complex terrain of Ondo State, Southwestern Nigeria

Abstract: The influence of lineaments, lineament intersections and geology on the groundwater yield of the basement terrain of Ondo State was investigated using optical remote sensing data, Aster DEM, geology, and borehole yield data. Landsat-7 ETM+ and Aster DEM were processed to generate composite lineament map. The study area was traversed by five (5) main lineament populations trending N-S, NE-SW, E-W, ENE-WSW, NNW-SSE. Boreholes sited on lineament exhibited a yield range of between 0.8 and 1.28 l/s with an average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Hydrogeological studies of the pre-Cretaceous Basement Complex Formations of Nigeria (Akinluyi et al 2018;Anderson and Ogilbee 1973;Olorunfemi and Oni 2019), revealed an average borehole yield of 14.67 gallons per sec (gps) from a mean depths of 37.49 m. Though, few boreholes in the unweathered rock, typically granite or gneiss produced more than a meager amount of water; in many wells, no water was found (Anderson and Ogilbee 1973). In contrast, wells tapping weathered granite and gneiss, where fully saturated, are found to yield the highest quantity of water (51.67 gps); the average yield for boreholes tapping battered rock was estimated to be around 23.33 gps per borehole (Anderson and Ogilbee 1973).…”
Section: Hydrogeological Settingmentioning
confidence: 99%
See 4 more Smart Citations
“…Hydrogeological studies of the pre-Cretaceous Basement Complex Formations of Nigeria (Akinluyi et al 2018;Anderson and Ogilbee 1973;Olorunfemi and Oni 2019), revealed an average borehole yield of 14.67 gallons per sec (gps) from a mean depths of 37.49 m. Though, few boreholes in the unweathered rock, typically granite or gneiss produced more than a meager amount of water; in many wells, no water was found (Anderson and Ogilbee 1973). In contrast, wells tapping weathered granite and gneiss, where fully saturated, are found to yield the highest quantity of water (51.67 gps); the average yield for boreholes tapping battered rock was estimated to be around 23.33 gps per borehole (Anderson and Ogilbee 1973).…”
Section: Hydrogeological Settingmentioning
confidence: 99%
“…3 The geological cross section of Sokoto Basin and the normal depth to water stand at about 6 m (Anderson and Ogilbee 1973). Generally, groundwater condition in the basement section of Sokoto Basin is typical of the Nigerian Basement Complex described by (Akinluyi et al 2018;Olorunfemi and Oni 2019).…”
Section: Hydrogeological Settingmentioning
confidence: 99%
See 3 more Smart Citations